A inserção da atividade turística em ambientes insulares do Brasil: um estudo de caso na Ilha dos Marinheiros - Rio Grande/RS - Porto, Pedro da Costa (2014)
This thesis aims to analyze the inclusion of tourism in the islands Brazil, drawing on a case study on the Ilha dos Marinheiros Rio Grande / RS, which occurred after the work of connecting the bridge to the mainland in 2004 . To achieve this goal, the research was divided into four stages. The first stage of the research is aimed at the definition of the materials and methods that were applied to the survey data required for the study. The second stage was dedicated to collect data in the field seeking acknowledgment of the study area and the approach to the local reality. During the second stage was also performed most of the literature review which allowed the theoretical foundations of the research. The main issues are: the history and transformation of culture and the Ilha dos Marinheiros, the genesis, evolution and delimitation of tourism; targeting this activity and characterization of tourism in the islands Brazil. The third and final stage of the research results obtained during organizing an exhibition of tourism in island environments of the parents and an analysis of this activity on the Ilha dos Marinheiros.